2020
DOI: 10.1021/acs.jchemed.0c00702
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Disruptions to the Teaching and Learning Equilibrium—Responsive Pedagogic Approaches to Teaching Online During the Covid-19 Pandemic in General Chemistry Classes at an Arabian Gulf University

Abstract: This reflection looks at pedagogic strategies employed in General Chemistry classes for English Language learners (ELLs) in a rapid response to the COVID-19 pandemic. The approaches included the use of small group systems thinking (ST) activities and a variety of formative assessments geared toward maintaining and enhancing students' language competencies, engagement, and motivation while studying in an online environment. The activities also allowed for prompt instructor feedback. Although the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…On the other hand, interviewees of various innovation adopter categories generally found online teaching and the preparation of online learning resources demand more time and effort, in comparison to the traditional face-to-face-only format. This sentiment is echoed by literatures about teachers’ opinions on online teaching [ 46 , 47 ], and some argued that developing a course with blended learning would take 2 to 3 times longer than a similar course in face-to-face-only format [ 48 , 49 ]. Some interviewees also mentioned that limited access to equipment and infrastructure was a key challenge in online teaching during the pandemic, and a small number of interviewees resorted to acquiring their own personal equipment to deliver online teaching at home.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…On the other hand, interviewees of various innovation adopter categories generally found online teaching and the preparation of online learning resources demand more time and effort, in comparison to the traditional face-to-face-only format. This sentiment is echoed by literatures about teachers’ opinions on online teaching [ 46 , 47 ], and some argued that developing a course with blended learning would take 2 to 3 times longer than a similar course in face-to-face-only format [ 48 , 49 ]. Some interviewees also mentioned that limited access to equipment and infrastructure was a key challenge in online teaching during the pandemic, and a small number of interviewees resorted to acquiring their own personal equipment to deliver online teaching at home.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The current cohort of students requires educators that can embrace cultural changes. Such adaptation and flexibility among faculty were later found to be critical during the institution's transition to the emergency remote learning situation created by the COVID-19 pandemic (Wilson, 2020).…”
Section: Symbolic Framementioning
confidence: 99%
“…Wilson found that there are great differences in online teaching mode of college English in different contexts. Therefore, an online teaching method based on adaptive changes of context is proposed [ 21 ]. To solve the problems of network Caton in the process of online English teaching, Kkese combined with 5 g data transmission technology and cloud storage technology proposed an end-to-end chaos method for online English teaching network, which effectively improved the video fluency and audio stability in the online English teaching process [ 22 ].…”
Section: Related Workmentioning
confidence: 99%